GADANG HOUSE IN DOCUMENTARY FILM OF THE ADAT NAGARI SIJUNJUNG DISTRICT - Fahriansyah, Elfit; Sasongko, Hery; Krishna, Adi (Capture : Jurnal Seni Media Rekam, 2018)
This documentary film entitled Perkampungan Adat Nagari Sijunjung (Traditional Village of Nagari Sijunjung) is trying to show the reality about the condition of the gadang house nowadays. This film was created with an expository documentary style, which uses the narrator as a single speaker. This documentary film describes one area that still maintains ‘gadang’ houses like their original functions, namely daily and customary functions. The daily function of the ‘gadang’ house is as a place to accommodate the daily activities of its inhabitants, as is usually the case with residential houses. While the traditional function of the ‘gadang’ house is the main house owned by a family belonging to a certain tribe. As the main house, the ‘gadang’ house is a place for traditional ceremonies and other importantevents from a large family of homeowners or fellow brothers of the same tribe.